Effect of pulsed electric fields on the production of yeast extract by autolysis. (August 2018) - Dimopoulos, Georgios; Stefanou, Nefeli; Andreou, Varvara; Taoukis, Petros
Abstract: The production of yeast extract by autolysis can be accelerated by treating yeast cell suspensions with pulsed electric fields (PEF) prior to autolysis. The present work is aimed at investigating the effects of PEF on the progress of yeast autolysis. Saccharomyces cerevisiae suspensions (8.3 log CFU/mL in distilled water) were subjected to various PEF treatment conditions (5–20 kV/cm, 1–2000 pulses, 15-μs pulse width) corresponding to various values of cell disintegration index (0–1). Suspensions were then autolyzed and the production of yeast extract was monitored in terms of total protein, amino acid and total solids release. PEF treatment led to an increase of final amino acid and total solids release of 37% and 20%, respectively. Autolysis was described mathematically by a first-order fractional model through which PEF treatment was found to accelerate the progress of autolysis up to 78% compared to untreated samples. Industrial relevance: The application of pulsed electric fields (PEF) for the production of yeast extract was studied. The standard lengthy autolysis procedure can be accelerated by the electroporation caused by PEF and increase the extract yield. The present study provides an exploration of the effects of PEF on the kinetics and yield of the autolysis procedure. Highlights: PEF treatment accelerated the process of autolysis by 78% compared to untreated samples Increasing the cell disintegration index decreased the characteristic release time of protein, total solids (60%) and amino acids (58%) Total solids and free α-amino nitrogen release yields of PEF treated samples increased by 20% and 37% respectively compared to untreated samples